Snowboarding: The construction of gender in an emerging sport - Anderson, K. L. (Journal of Sport and Social Issues, 1999)
Previous research has identified sport as a practice that creates and legitimizes notions of male dominance. However, gender is constructed and resisted differently within various sporting activities. This article addresses the diversity of masculinities in sport through an exploration of the construction of gender in an emerging sport—snowboarding. The analysis identifies four social practices used by male snowboarders to construct their sport as a masculine practice: (a) appropriation of other cultural masculinities, (b) interaction and clothing styles, (c) violence and aggression, and (d) emphasized heterosexuality. The findings indicate that the historical context of snowboarding and the social class, race-ethnicity, and age of snowboarding participants influence the social practices used to create masculinity. Although snowboarders rely on different social practices to construct masculinity than those used in organized sports, these practices also serve to support notions of male dominance and difference from women.